Rebiopsy of non–small cell lung cancer patients with acquired resistance to epidermal growth factor receptor‐tyrosine kinase inhibitor: Comparison between T790M mutation‐positive and mutation‐negative populations. Issue 24 (16th September 2013) - Hata, Akito; Katakami, Nobuyuki; Yoshioka, Hiroshige; Takeshita, Jumpei; Tanaka, Kosuke; Nanjo, Shigeki; Fujita, Shiro; Kaji, Reiko; Imai, Yukihiro; Monden, Kazuya; Matsumoto, Takeshi; Nagata, Kazuma; et al.
Abstract : BACKGROUND: The secondary epidermal growth factor receptor (EGFR) mutation Thr790Met (T790M) accounts for approximately half of acquired resistances to EGFR‐tyrosine kinase inhibitor (TKI). Recent reports have demonstrated that the emergence of T790M predicts a favorable prognosis and indolent progression. However, rebiopsy to confirm T790M status can be challenging due to limited tissue availability and procedural feasibility, and little is known regarding the differences among patients with or without T790M mutation. METHODS: The study investigated 78 EGFR ‐mutant patients who had undergone rebiopsy after TKI failure. The peptide nucleic acid–locked nucleic acid polymerase chain reaction clamp method was used in EGFR mutational analyses. Various patient characteristics and postprogression survivals (PPSs) after initial TKI failure were retrospectively compared in patients with and without T790M. RESULTS: The T790M mutation was identified in 4 (17%) of 24 central nervous system lesions, and in 22 (41%) of 54 other lesions ( P = .0417). No other characteristics had a statistical association with T790M prevalence. Median PPS was 31.4 months in 26 patients with T790M, and 11.4 months in 52 patients without T790M ( P = .0017). In the multivariate analysis, statistically significant factors for longer PPS included T790M‐positive, good performance status, and no carcinomatous meningitis. CONCLUSIONS: The emergence of T790M in central nervous system lesions was rare, compared with other lesions. Patients with T790M after TKI failure appear to have better prognoses than those without T790M. TKI rechallenge or continuous administration beyond progression may be effective after initial TKI failure. Cancer 2013;119:4325–4332 . © 2013 American Cancer Society . Abstract : Rebiopsy to confirm T790M status can be challenging due to limited tissue availability and procedural feasibility, and little is known regarding the differences among patients with or without T790M. Results of this study demonstrated low prevalence of T790M in central nervous system and prognostic impact of T790M after acquired resistance to epidermal growth factor receptor‐tyrosine kinase inhibitor.